Parental perception of children's privacy in smart toys in countries of different economic levels. (February 2023) - Pinheiro Amâncio, Fernanda Maria; Souza, Ana Paula; Fantinato, Marcelo; Peres, Sarajane Marques; Hung, Patrick C.K.; Coutinho do Rêgo, Luis Gustavo; Roa, Jorge
Abstract: Smart toys pose potential privacy risks, which may lead to aversion of parents who may choose not to buy them for their children. Magazine and newspaper articles have recently discussed these risks. However, in developing economies, these toys are not yet widely marketed, and hence the result may be different, perhaps due to potential consumer ignorance of new technology. To investigate this scenario, we conducted an empirical study in the form of a survey that was responded by 599 participants from advanced and developing economies. According to the responses, while most participants believe smart toy technology has positive aspects in terms of innovation, most of them also show a high level of concern about children's privacy when using such smart toys. The main concern is the need for parental control when a child is playing with a smart toy with internet access. Overall, the negative perception is higher among participants from advanced economies. The countries that most contributed participants to this survey were Brazil and Argentina (developing economies) and the USA and Canada (advanced economies). Highlights: We evaluated the perception of parents on children's privacy regarding smart toys. We compared consumers from countries at different levels of economic development. Both developed and developing economies showed a negative perception. Parents from developing economies showed a less negative perception.